2006
DOI: 10.1111/j.1471-4159.2006.03997.x
|View full text |Cite
|
Sign up to set email alerts
|

SNAP25 is a pre‐synaptic target for the depressant action of reactive oxygen species on transmitter release

Abstract: Reactive oxygen species (ROS) participate in various physiological and pathological processes in the nervous system, but the specific pathways that mediate ROS signalling remain largely unknown. Using electrophysiological techniques and biochemical evaluation of isolated fusion proteins, we explored the sensitivity to standard oxidative stress of the entire synapse, the pre-synaptic machinery and essential fusion proteins underlying transmitter exocytosis. Oxidative stress induced by H 2 O 2 plus Fe 2+ inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 52 publications
(122 reference statements)
2
71
0
Order By: Relevance
“…In guinea pig striatal slices, H 2 O 2 production was Ca 2+ -dependent and modulated neurotransmitter release, revealing a signaling role for ROS in synaptic transmission [154]. A possible target is the fusion protein SNAP25, which may function as a presynaptic ROS sensor [155].…”
Section: Nox Enzymes In Brain and Nerve A Roles For Nox-derived Ros mentioning
confidence: 99%
“…In guinea pig striatal slices, H 2 O 2 production was Ca 2+ -dependent and modulated neurotransmitter release, revealing a signaling role for ROS in synaptic transmission [154]. A possible target is the fusion protein SNAP25, which may function as a presynaptic ROS sensor [155].…”
Section: Nox Enzymes In Brain and Nerve A Roles For Nox-derived Ros mentioning
confidence: 99%
“…This phenomenon was recently linked to increased Cdk5 kinase activity that occurs in response to oxidative stress [86] . In addition, free radicals have been shown to inhibit synaptic vesicle release, through interference with SNARE assembly at motor nerve terminals [87] . Experimental inhibition of vesicle release by a similar mechanism, using botulinum toxin, has been shown to cause synapse withdrawal and even cell death in CNS neurons [88] .…”
Section: Rosmentioning
confidence: 99%
“…This process requires formation of a tight ternary complex between the vesicular (v) SNARE, termed synaptobrevin (or VAMP, vesicle-associated membrane protein), and 2 membrane target (t)-SNARE, known as syntaxin and SNAP-25 on the cytosolic surface of the plasma membrane (46). Interestingly, recent studies have shown that reactive oxygen species impair acetylcholine release, independent of G-protein cascades, through presynaptic functioning of SNAP-25 as a reactive oxygen species sensor (47). Possibly, this may provide a link between the role of DHA in protection against oxidative stress (24) and in altering neurotransmission (23), including acetylcholine (48).…”
Section: Introductionmentioning
confidence: 99%